"They Died the Spartan's Death": Thermopylae, the Alamo, and the Mirrors of Classical Analogy. Issue 3 (1st September 2016) - Cox, Jeremy
ABSTRACT: In moments of crisis, people often make sense of the present by activating memories of the past through particular tropes of public memory. Classical analogies are one such trope, suggesting a sense of continuity between a (seemingly) stable ancient world and a chaotic present. Despite their prominence in American rhetoric, classical analogies have received too little attention from scholars of rhetoric. In the following, I interrogate the use of classical analogies in nineteenth-century American rhetoric— a period in which the classics were a vibrant aspect of public culture—by analyzing analogies between the fall of the Alamo and the fifth-century BC battle of Thermopylae. Thermopylae analogies were activated as tropes of public memory to warrant the formation of a defiant political identity for a Texian community reeling from defeat. Through an analysis of key texts that utilized Thermopylae analogies, I show that classical analogies sometimes go beyond comparisons between the past and the present to act as "mirrors" that inspire identification with, and imitation of, the ancients.